2020
DOI: 10.1370/afm.2518
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Primary Care Research: A Scoping Review

Abstract: PURPOSE Rapid increases in technology and data motivate the application of artificial intelligence (AI) to primary care, but no comprehensive review exists to guide these efforts. Our objective was to assess the nature and extent of the body of research on AI for primary care. METHODSWe performed a scoping review, searching 11 published or gray literature databases with terms pertaining to AI (eg, machine learning, bayes* network) and primary care (eg, general pract*, nurse). We performed title and abstract an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 55 publications
3
90
0
3
Order By: Relevance
“…Worldwide, there is a great deal of interest in AI techniques and their potential in medicine, not least in the United Kingdom where politicians and NHS leaders have publicly prioritized the incorporation of AI into clinical settings. Our findings support those of Kueper et al [ 17 ], namely, that although some AI techniques have good initial validation reports, they have not yet been through the steps for full application in clinical practice. Validation using independent data is preferable to splitting a single data set [ 185 ] and could be the next step in the development of many AI techniques identified in this review.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Worldwide, there is a great deal of interest in AI techniques and their potential in medicine, not least in the United Kingdom where politicians and NHS leaders have publicly prioritized the incorporation of AI into clinical settings. Our findings support those of Kueper et al [ 17 ], namely, that although some AI techniques have good initial validation reports, they have not yet been through the steps for full application in clinical practice. Validation using independent data is preferable to splitting a single data set [ 185 ] and could be the next step in the development of many AI techniques identified in this review.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies of AI-based techniques for the early detection of cancer have been undertaken in primary care settings [ 17 ]. Therefore, the aim of this systematic review is to identify AI techniques that facilitate the early detection of cancer and could be applied to primary care EHR data.…”
Section: Introductionmentioning
confidence: 99%
“…Confirming this, a review on artificial intelligence (AI) in primary care indicated that only 14% of published studies reporting development of AI diagnostic or treatment support algorithms had authors who were employed in primary care [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, application of AI appeared to enable more personalized care pathways based on personal health profiles [18]. The COVID-19 pandemic requires existing health care models to have better integration, delivery, and distribution capabilities, and thus, new requirements for AI in eHealth have been put forward [18,28,29]. Thus far, the main fields that AI technology has been applied to during the pandemic is early detection and diagnosis of infections, personal contact tracking, case and mortality prediction, drug and vaccine development, reducing the workload of medical staff, and other aspects of controlling and managing the spread of the virus [23].…”
Section: Potential Of Artificial Intelligencementioning
confidence: 99%